PENGARUH PEMBERIAN FERMENTASI KOTORAN AYAM ROTI AFKIR DAN AMPAS TAHU DALAM MEDIA KULTUR MASSAL TERHADAP PERTUMBUHAN DAN KANDUNGAN NUTRISI Daphnia sp. - Zumalallail Nailulmuna; Pinandoyo Pinandoyo; Vivi Endar Herawati (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2017)
This research was aimed to found out the effect of fermented quail feces, bread waste, and tofu and determine the best treatment to generate the biomass growth, and the nutrition content of the Daphnia sp. This research used laboratory animals such as Daphnia sp. and a container of concrete tanks as many as four. The methods of this research was used experimental methods with Complete Randomize Design with 4 treatments and population count repetition as 3 times with the density of the Daphnia sp. was 100 ind./l. Treatments of this research were Tretment A (0 % chicken mannure, 50 % tofu waste and 50 % bread waste), B (25 % chicken mannure, 50 % tofu waste and 25 % bread waste), C (25 % chicken mannure, 25 % tofu waste and 50 % bread waste, D (50 % chicken mannure, 25 % tofu waste and 25 % bread waste) with the total amount of the combination was 200 g/l. Data which observed were population density, biomass, and nutrition content. The results showed that the treatment of A was the lowest population density valued 548.67 ind / ml and the highest population density was on C treatment with a density of 1328.67 ind / ml at the peak of the stationary phase. Biomass in treatment C resulted in 336.30 grams and the treatment A yield 82.64 grams, and the content of nutrients with the highest protein is found in the C treatment with a value of 66.80%.Keywords : Daphnia sp.; chicken manure; tofu waste; bread waste; fermentation